Application of reinforced three-phase-foams in UHPC foam concrete. (30th January 2017) - Krämer, Christina; Schauerte, Matthias; Müller, Torsten; Gebhard, Sören; Trettin, Reinhard
Highlights: Implementation of three-phase-foams with and without nanotubes was successfully done. Especially improved mechanical properties can be reached by three-phase-foams. Surface properties of used nanomaterials/surfactant and formed products were studied. Influences on morphology/carbonation and properties of foam concretes were shown. Abstract: Over the last years lightweight materials received considerable attention due to their invincible properties. Hereby, cost through materials saving, combination of thermal insulation with mechanical properties and sustainability are enabled. To reach also statical relevance but still achieve certain thermal properties, mainly aerated concretes are applied. One way to obtain comparable properties without cost intensive autoclaving is the application of UHPC approach. Another way to further enhance the performance of foam concretes are inorganic foams based on three phases which provide strengthening through pozzolanic reaction. Here, electrostatic interactions between solid particles and surfactants provide high foam stability. The combination of UHPC approach and implementation of three-phase-foams showed significant improvement of especially mechanical properties. Additionally, nanotubes were used to further improve performance of resulting foam concretes due to nanoreinforcement and their nucleation abilities. Before implementation of inorganic foams in the mortar, surface properties of used surfactant and nanomaterials as well as their influence on hydration products were investigated in a model system. Differences in their impact on hydration products and interactions among themselves were observed. Finally, reinforced three-phase-foams were successfully integrated and mainly focused mechanical properties improved. Results of the phase development, microstructure and mechanical properties of UHPC foam concretes are illustrated and discussed.